2009
DOI: 10.1111/j.1439-0469.2008.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and ultrastructural analyses of the chromosomes ofDiscocyrtus pectinifemur(Opiliones, Laniatores, Gonyleptidae)

Abstract: Among the Opiliones, species of the suborders Cyphophthalmi, Eupnoi, Dyspnoi and Laniatores have shown very diverse diploid chromosome numbers. However, only certain Eupnoi species exhibit XY⁄XX and ZZ⁄ZW sex chromosome systems. Considering the scarcity of karyotypical information and the absence of structurally identifiable sex chromosomes in the suborder Laniatores, we decided to analyse the chromosomes and bivalents of Discocyrtus pectinifemur (Gonyleptidae) to identify possible sex differences. Testicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(42 reference statements)
1
6
0
Order By: Relevance
“…The absence of morphologically differentiated sex chromosomes (i.e., homomorphic) is not an exclusive feature of the Amblypygi species investigated here, but it has also been recorded in all scorpions and in most harvestmen cytogenetically characterized (Schneider et al, 2008(Schneider et al, , 2009a. Král et al (2008) demonstrated the absence of morphologically differentiated sex chromosomes in Palpigradi species, an arachnid order with numerous primitive characters, and proposed that this condition could constitute an ancestral state for Arachnida.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of morphologically differentiated sex chromosomes (i.e., homomorphic) is not an exclusive feature of the Amblypygi species investigated here, but it has also been recorded in all scorpions and in most harvestmen cytogenetically characterized (Schneider et al, 2008(Schneider et al, , 2009a. Král et al (2008) demonstrated the absence of morphologically differentiated sex chromosomes in Palpigradi species, an arachnid order with numerous primitive characters, and proposed that this condition could constitute an ancestral state for Arachnida.…”
Section: Discussionmentioning
confidence: 99%
“…The number and location of NORs were only established, for example, in approximately 30 species of Araneae (Král et al, 2006;Král, 2007;Oliveira et al, 2007;Rodríguez-Gil et al, 2007;Araujo et al, 2008;Stávale et al, 2010Stávale et al, , 2011Dolejš et al, 2011;Král et al, 2011), 17 species of Scorpiones (Schneider et al, 2009a,b;Schneider and Cella, 2010), 3 species of Opiliones (Gorlov and Tsurusaki, 2000;Oliveira et al, 2006;Schneider et al, 2008;Mattos et al, 2013), and two species of Palpigradi (Král et al, 2008). In almost all these species, the NORs were only identified through the use of silver impregnation; however, in an overview of the NOR distribution in Coleoptera, Schneider et al (2007) showed that the results were usually coincident when the chromosomes were examined with both silver impregnation and FISH technique.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, data from both silver staining [e.g. Gunn and Hilburn, 1989;Král et al, 2008;Schneider et al, 2008] and FISH [Hill et al, 2009;Meyer et al, 2010;Schneider and Cella, 2010] indicate that one NOR pair is the most common pattern in arachnids. Therefore, one NOR pair could be the ancestral characteristic of this class.…”
Section: Discussionmentioning
confidence: 99%
“…In harvestmen, the number and the distribution of rDNA loci have up to now only been examined by means of silver staining of nucleolar argyrophilic proteins, hence detecting only transcriptionally active rDNA clusters [Gorlov and Tsurusaki, 2000b;Oliveira et al, 2006;Schneider et al, 2008]. Only a single rDNA cluster was visualized in a diploid set of Psathyropus tenuipes (L. Koch, 1878) (Sclerosomatidae) [Gorlov and Tsurusaki, 2000b] and Dyscocyrtus pectinifemur (Mello-Leitão, 1937) (Gonyleptidae) [Schneider et al, 2008], while 1 pair of rDNA loci was noted in Goniosoma spelaeum (Mello-Leitão, 1932) [Oliveira et al, 2006]. In other arachnid orders, the data on the number and the position of rDNA are still fragmentary, too.…”
Section: Discussionmentioning
confidence: 99%